2016
DOI: 10.1158/0008-5472.can-16-0356
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HOXA11-AS Promotes Proliferation and Invasion of Gastric Cancer by Scaffolding the Chromatin Modification Factors PRC2, LSD1, and DNMT1

Abstract: Long noncoding RNAs (lncRNA) have been implicated in human cancer but their mechanisms of action are mainly undocumented. In this study, we investigated lncRNA alterations that contribute to gastric cancer through an analysis of The Cancer Genome Atlas RNA sequencing data and other publicly available microarray data. Here we report the gastric cancer-associated lncRNA HOXA11-AS as a key regulator of gastric cancer development and progression. Patients with high HOXA11-AS expression had a shorter survival and p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
390
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 437 publications
(395 citation statements)
references
References 54 publications
5
390
0
Order By: Relevance
“…Here, RNA pull down and RIP assays demastrated that Linc00441 could bind to DNMT1 in GC cells ( Figure 5). As well as our findings, Sun et al have found that lncRNA HOXA11-AS stimulates cell proliferation and metastasis of GC via scaffolding the chromatin modification factors PRC2, LSD1 and DNMT1 [32]. Wang et al have found that lncRNA Dum inhibits Dppa2, its adjacent gene, in cis by recruiting DNMT1, DNMT3A and DNMT3B [33].…”
Section: Discussionsupporting
confidence: 89%
“…Here, RNA pull down and RIP assays demastrated that Linc00441 could bind to DNMT1 in GC cells ( Figure 5). As well as our findings, Sun et al have found that lncRNA HOXA11-AS stimulates cell proliferation and metastasis of GC via scaffolding the chromatin modification factors PRC2, LSD1 and DNMT1 [32]. Wang et al have found that lncRNA Dum inhibits Dppa2, its adjacent gene, in cis by recruiting DNMT1, DNMT3A and DNMT3B [33].…”
Section: Discussionsupporting
confidence: 89%
“…S7A). Some lncRNAs affect the expression of protein-coding genes by interacting with the PRC2 subunit EZH2 (32)(33)(34). In starBase v2.0, we found that EZH2 in murine embryonic stem cells could bind to Neat1 (http:// starbase.sysu.edu.cn/; Supplementary Fig.…”
Section: Neat1 Interacts With Ezh2mentioning
confidence: 99%
“…Sun et al reported that patients with high HOXA11‐AS expression had a shorter survival and poorer prognosis 24. HOXA11‐AS alterations showed a complexly integrated phenotype affecting cell growth, migration, invasion, and apoptosis both in vitro as well as in vivo.…”
Section: Hoxa11‐as Lncrna In Human Cancersmentioning
confidence: 99%